PENGARUH UKURAN KOMITE AUDIT, KOMITE AUDIT INDEPENDEN DAN DEWAN PENGAWAS SYARIAH TERHADAP MANAJEMEN LABA PADA PERBANKAN UMUM SYARIAH PERIODE 2010-2012 - Rahmad Sahami; Mirna Dyah P (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2015)
This study examines the effect of audit committee, independent auditcommittee, and shariah supervisory boar on earnings management inIndonesia sharia banking. Population in this study were all Islamic banks inIndonesia, which fully published annual report for the year 2010-2012 andhas complete data about the profile of audit committee and the shariasupervisory board. Based on purposive sampling method, 33 samples wereobtained by observation data. Secondary data was collected throughdocumentation and analyzed with multiple linearregressionanalysis.Theresults of this study indicate that numbers of audit committee andindependent audit committee has significant influence on earningsmanagementinIndonesiashariabanking.ButTheSharia Supervisory Board has to significant effect on earningsmanagement in Indonesia sharia banking.